PENENTUAN EFISIENSI DYE SENSITIZED SOLAR CELL (DSSC) MENGGUNAKAN EKSTRAK BUAH KAKTUS (Opuntia elatior Mill.) - Christianto Pasunu; Ruslan Ruslan; Hardi Ys. (KOVALEN: Jurnal Riset Kimia, 2017)
Dye-Sensitized Solar Cells (DSSC) research by using cactus fruit extract (Opuntia elatior Mill.) has been done. The objectives of the research are to determine the highest efficiency of submersion time and Dye pH treatments of cactus fruit extract (Opuntia elatior Mill.). This research was used a Complete Random Design (CRD) method whereas the submersion time of the worked electrode on five extents of treatments are 6,12,18, 24, 30 hours and Dye pH on four extents of treatments are 1, 3, 5, and 7. The result showed that the optimum time at 12 hours with the Dye pH at 3 has resulted in the highest efficiency of 0.105. Keywords: Cactus fruit extract, Opuntia elatior Mill, efficiency, DSSC.